Literature review of the benefits and obstacle of Horizontal Directional Drilling - Md. Salleh, Mohd. Norizam; Haron, Nuzul Azam; Mohd Shafri, Helmi Zulhaidi; Abdullah, Abdul Aziz; Ahmad, Nadzrol Fadzilah (2017)
In this new era the construction industry not only need to be completed within budget, timely, at acceptable quality and safety but the stakeholders especially the local authorities and the public realises for the important need of sustainable construction method to be used for our younger generation to heritage if not better a safer world for them to live and raise up their children's. Horizontal Directional Drilling method is the most commonly recognised trenchless utilities method as a preferred construction method in this age. Among the reasons HDD method offers less disturbance on traffic, the public, business activities and neighbourhood, lower restoration cost, less noise, dust and minimum import/export of the construction materials. In addition HDD method can drill through congested utilities areas with minimum cutting and shorter time. This paper aims to appraise the benefits and obstacle of HDD method in construction industry. It is an endeavour to fulfil the local authorities cry for alternative method that less damages to the roads, road furniture's and public complaints compared to the conventional open cut method. In addition HDD method is seem to be in line with sustainable development requirements e.g. reduce, reuse, recycle and etc. Hence, it is important to determine the benefits and obstacle factors of HDD implementation. The factors are based on the literature review conducted by the author on the subject matters gathered from previous studies, journals, text books, guidelines, magazine articles, newspaper cutting and etc.